Clinical characteristics and outcome in dogs with small cell T‐cell intestinal lymphoma. (11th January 2018) - Couto, K. M.; Moore, P. F.; Zwingenberger, A. L.; Willcox, J. L.; Skorupski, K. A.
Abstract : Small cell intestinal lymphoma has not been well characterized in dogs. The objective of this study was to describe clinical characteristics and outcome in dogs with small cell intestinal lymphoma. We hypothesized that affected dogs would have prolonged survival compared with high‐grade gastrointestinal (GI) lymphoma. Pathology records were searched for dogs with histologically confirmed small cell GI lymphoma. Seventeen dogs with confirmed small cell intestinal lymphoma were identified, and clinical and outcome data were retrospectively collected. Histopathology was reviewed by a board‐certified pathologist, and tissue sections were subjected to immunophenotyping and molecular clonality assessment. All dogs had small cell, T‐cell, lymphoma confirmed within various regions of small intestine, with 1 dog also having disease in abdominal lymph nodes. All dogs had clinical signs attributable to GI disease; diarrhoea ( n = 13) was most common. Ultrasonographic abnormalities were present in 8 of 13 dogs with abnormal wall layering ( n = 7) and hyperechoic mucosal striations ( n = 7) representing the most common findings. In total, 14 dogs received some form of treatment. The median survival time (MST) for all dogs was 279 days and the MST for the 14 dogs that received any treatment was 628 days. Dogs with anaemia and weight loss at presentation had significantly shorter survival times and dogs that received a combination of steroids and an alkylating agent had significantly longer survival times. Small cell, T‐cell, intestinal lymphoma is a distinct disease process in dogs, and those undergoing treatment may experience prolonged survival.